Would Liberalization Lead to Epidemic Cocaine Consumption? - Loayza, Norman V.; Sugawara, Naotaka (Taylor and Francis, 2013)
This article uses cross-country data to estimate the potential effect of drastic reductions in the price of cocaine on the share of the population that consumes this drug. In order to identify movements along the cocaine consumption/demand function, this article instruments for cocaine prices with variables that affect the supply of cocaine. Liberalization of drug policies would produce an increase in the prevalence of cocaine consumption. However, the quantitative evidence presented here suggests that, even if substantial, this increase would not amount to epidemic cocaine use.